PENANGGULANGAN PERDAGANGAN PEREMPUAN DI PERBATASAN ENTIKONG KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT: PERSPEKTIF KEAMANAN MANUSIA - Elyta Elyta (Indonesian Journal of Dialectics, 2012)
This research is about prevention of trafficking based on human security perspective. There most important thing connected to human security issues is the prevention of woman trafficking is not effective This study used a qualitative method. Primary and secondary data collections were used to collect the data. Primary data were obtained by interview and observation, while secondary data were collected from document and articles. Data analysis is covered data collection, reduction, display of data, and inferences.This study found that woman trafficking from the risk assessment’s point of view has become a threat to human security. It is noted that the implementation of women trafficking prevention did not work out as expected.  The prevention that has been done from the government are involves enhancement of education supervision of border. Those activities actually did not touch the grass-root women from Entikong that vulnerable to women trafficking. Moreover, the protection from the local government of Sanggau district which cooperated with non government organizations is running spatially.